Skin-Inspired Humidity and Pressure Sensor with a Wrinkle-on-Sponge Structure - Miao, L; J Wan; Y. Song; H. Guo; Chen, H.; Cheng, X; H. Zhang (ACS Applied Materials & Interfaces, 2019)
Sensors with multifunctions have attracted great attention for their extensive application value, among which humidity sensing and pressure sensing are necessary to electronics undoubtedly because of the complex physical environment we live in. Inspired by the structure of skin, in this article, we design a new method to combine wrinkle structure with porous sponge structure and achieve a novel, flexible, compressible, and bifunctional sensor based on carbon nanotube–polydimethylsiloxane (CNT–PDMS) with functions of humidity sensing and pressure sensing. The performance of the humidity sensing part can be controlled by the ultraviolet and ozone (UVO) treatment time and CNT concentration, while the sensitivity of the pressure sensing part can be controlled by the CNT concentration and grinding time of sugar granules. The bifunctional sensorcan easily sense approaching and touching of a hand, which shows great potential of alarming and protecting some electronics. Moreover, the bifunctional sensor can also be used in detecting human joint motions and breath conditions as a wearable and flexible health monitor.